2012
DOI: 10.1007/978-3-642-23562-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Last-Mile e-Grocery Urban Distribution: Have New B2C Trends a Positive Impact on the Environment?

Abstract: The business to consumer distribution services (B2C), mainly related to ecommerce, know nowadays a real boom that is sometimes accompanied by fractures. To better understand this fast-changing situation and support researchers and practitioners, this chapter proposes a scenario assessment analysis focused on the new B2C strategy trends and the joint coordination of e-commerce stakeholders to better optimize consumer's delivery flows. First, the two main logistics solutions adopted by online retailers are intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Wird der Transport allerdings selbst organisiert, so werden in der Regel deutlich größere und emissionsintensivere Fahrzeuge verwendet als private PKW, z. B. etwa 228 gCO2e/km für leichtes Nutzfahrzeug wie 3,5 t Transporter (González-Feliu et al, 2013;Marcucci et al, 2021). Anders als bei Privattransporten muss außerdem, aufgrund der längeren Strecke und höheren Transportdauer, die Kühlkette der Lebensmittel aufrechterhalten werden.…”
Section: Zentrale Auslieferungunclassified
See 1 more Smart Citation
“…Wird der Transport allerdings selbst organisiert, so werden in der Regel deutlich größere und emissionsintensivere Fahrzeuge verwendet als private PKW, z. B. etwa 228 gCO2e/km für leichtes Nutzfahrzeug wie 3,5 t Transporter (González-Feliu et al, 2013;Marcucci et al, 2021). Anders als bei Privattransporten muss außerdem, aufgrund der längeren Strecke und höheren Transportdauer, die Kühlkette der Lebensmittel aufrechterhalten werden.…”
Section: Zentrale Auslieferungunclassified
“…B. wird die Umweltauswirkung erhöht, wenn "Nahversorger", die eigentlich zu Fuß einkaufen, zum Online-Handel wechseln, da die Preise geringer sind). Weiterhin scheint die zentralisierte Lieferung in peripheren Gegenden mit geringer Einzelhandels-und hoher Haushaltsdichte besonders hohe CO2-Einsparungen zu ermöglichen (Astash-kina et al, 2019;González-Feliu et al, 2013). Damit übereinstimmend kommen Wygonik & Goodchild (2018) zu dem Schluss, dass die Straßendichte und die Entfernung zum Zentrallager die ausschlaggebenden Faktoren für den Unterschied in den Emissionen sind.…”
Section: Zentrale Auslieferungunclassified
“…While the internet offers great opportunities for direct selling, it also raises serious challenges related to order fulfilment. González-Feliu et al, (2012) observed that many online retailers find delivery of orders made online to be a particularly challenging task. Proper management of order fulfilment can be a good source of competitive advantage.…”
Section: Perceived Expertise In Order Fulfilmentmentioning
confidence: 99%
“…It was then logical from the urban standpoint that attention was paid to the prominent economic/environmental aspect: high cost due to frequent stops correlated with growing pollution (Ségalou et al, 2004;Gonzalez-Feliu and Morana, 2010;Dablanc and Rakotanarivo, 2010;Gonzalez-Feliu et al, 2012). The perspective then shifted to improving collaborative logistics practices (Gonzalez-Feliu et al, 2013;Carbone and Blanquart, 2014 -the application of SSCM from the economic standpoint is based mainly on intra-and interorganizational connections.…”
Section: Taking Into Account the Managerial Interest Of Sustainable Smentioning
confidence: 99%